(untitled) (International Seven Journal of Multidisciplinary, 2025)
This study investigates the deposition of titanium nitride (TiN) thin films by cathodic cage plasma discharge on glass substrates at low temperature (300 °C) and short substrate-to-lid distance (7 mm), aiming to evaluate the effect of the H₂/N₂ ratio in the plasma on the film properties. Depositions were carried out at 1 Torr, and the films were characterized by X-ray diffraction, X-ray reflectometry, and electrochemical impedance spectroscopy (EIS). It was observed that the deposition rate is influenced by the H₂/N₂ proportion, with adequate hydrogen content favoring higher growth rates. EIS analysis enabled the estimation of electrical resistivity and chemical stability, revealing deposition conditions that enhance corrosion resistance. The novelty of this work lies in the combination of: (i) a cathodic cage geometry with a high number of holes; (ii) a short 7 mm substrate-to-lid spacing that intensifies hollow-cathode effects; and (iii) an electrochemical approach (EIS) to correlate process, microstructure, and properties.